An Assessment of Perceived Antecedents to Attitudes of College Students towards Children with Autism - Park, Meungguk; Chitiyo, Morgan; Huh, Changdeog; Zeleke, Waganesh (Journal of the American Academy of Special Education Professionals, 2019)
This study examined the extent to which six antecedent variables influenced college students’ attitudes towards autism. A comprehensive literature review and factor analysis identified the six perceived antecedents, including "learning and volunteer experience," "family/friends with autism," "parental role," "exposure to children with autism," "mass media influence," and "inclusion belief toward autism." A total 195 college students participated in the study. Results of multiple regression analyses indicated that the regression model was significant (p < 0.001), and the six antecedent variables explained 18% of the variance. "Inclusion belief" was found to be a significant predictor of attitudes ([beta] = 0.32, p < 0.01). In addition, "gender," "student major," "personal learning" and "volunteer experience" were found to influence personal attitudes.